Measurement of the transverse momentum spectra of weak vector bosons produced in proton-proton collisions at $ \sqrt{s}=8 $ TeV - CMS collaboration (2300 authors) (2017)
The transverse momentum spectra of weak vector bosons are measured in the CMS experiment at the LHC. The measurement uses a sample of proton-proton collisions at $ \sqrt{s}=8 $ TeV, collected during a special low-luminosity running that corresponds to an integrated luminosity of 18.4 ± 0.5 pb$^{−1}$. The production of W bosons is studied in both electron and muon decay modes, while the production of Z bosons is studied using only the dimuon decay channel. The ratios of W$^{−}$ to W$^{+}$ and Z to W differential cross sections are also measured. The measured differential cross sections and ratios are compared with theoretical predictions up to next-to-next leading order in QCD.